2020
DOI: 10.2196/22532
|View full text |Cite
|
Sign up to set email alerts
|

Internet-of-Things Skills Among the General Population: Task-Based Performance Test Using Activity Trackers

Abstract: Background The health internet-of-things (IoT) can potentially provide insights into the present health condition, potential pitfalls, and support of a healthier lifestyle. However, to enjoy these benefits, people need skills to use the IoT. These IoT skills are expected to differ across the general population, thereby causing a new digital divide. Objective This study aims to assess whether a sample of the general Dutch population can use health IoT by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Since social robots are still not widely adopted, we consider scientific interest as a proxy for knowledge and awareness of social robots—and technology skills with social robots. Extant research has shown that (digital) technology skills vary by education (Van Deursen and Van Dijk, 2011 ; De Boer et al, 2020 ). Based on De Boer et al ( 2020 ) study about internet-of-things technologies, which share similarities with social robots, we expect technology skills with social robots to vary by education level as well.…”
Section: Model and Theoretical Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Since social robots are still not widely adopted, we consider scientific interest as a proxy for knowledge and awareness of social robots—and technology skills with social robots. Extant research has shown that (digital) technology skills vary by education (Van Deursen and Van Dijk, 2011 ; De Boer et al, 2020 ). Based on De Boer et al ( 2020 ) study about internet-of-things technologies, which share similarities with social robots, we expect technology skills with social robots to vary by education level as well.…”
Section: Model and Theoretical Developmentmentioning
confidence: 99%
“…Extant research has shown that (digital) technology skills vary by education (Van Deursen and Van Dijk, 2011 ; De Boer et al, 2020 ). Based on De Boer et al ( 2020 ) study about internet-of-things technologies, which share similarities with social robots, we expect technology skills with social robots to vary by education level as well. Given that scientific interest and technology skills are both shaped by someone's education, we think it is justifiable to use scientific interest as a proxy for technology skills with social robots, particularly in a situation where individuals do not have experience with the technology itself (i.e., they do not own a robot).…”
Section: Model and Theoretical Developmentmentioning
confidence: 99%
“…Users of IoT home automation need to know what platform-app, website, or a central platform-can provide them with access to the data they are searching for. To identify and select these data in the IoT's infinitive dataset, they require a clear idea of which data are relevant to their envisioned goal (Atzori et al, 2010;De Boer et al, 2020). Once the relevant data have been identified, users must be able to determine what format is the most suitable to present the data in an understandable manner.…”
Section: Data Skillsmentioning
confidence: 99%
“…With regard to previous web developments, strategic skills can be divided into four distinct steps of decision-making: orienting goals, taking required actions, making decisions, and implementing decisions (Van Deursen et al, 2021). To fit the context of IoT wherein the devices play a larger role in the decisionmaking process, De Boer et al (2020) translated these steps to (1) orientating goals, (2) combining data with other information sources, (3) making data-driven decisions and assessing automated (or proposed) actions of the IoT, and (4) taking actions and reflecting upon the actions of the IoT.…”
Section: Data Skillsmentioning
confidence: 99%
See 1 more Smart Citation